Urinary microbiome and urological cancers: a mini review - Randazzo, Gianmarco; Bovolenta, Eleonora; Ceccato, Tommaso; Reitano, Giuseppe; Betto, Giovanni; Novara, Giacomo; Iafrate, Massimo; Morlacco, Alessandro; Dal Moro, Fabrizio; Zattoni, Fabio (Frontiers in Urology, 2024)
IntroductionThe urinary microbiome (UMB) includes living bacteria, their genomes, and their products from interactions with the host environment. A “core” UMB could potentially exist, with variations between age and sex groups. Changes in UMB composition have been associated with benign urological disorders, but also with urologic cancers. Mechanisms through which UMB can trigger and maintain cancer can be local inflammation and interaction with immune system.Aim of the studyTo describe the association between UMB and development of urologic cancers.MethodsA non-systematic literature review identified recently published studies (last 5 years), involving human patients, dealing with UMB. The database used for this review was PubMed, and the identified studies served as the base for a narrative analysis of the literature that explored the potential associations between UMB and urological cancers.ResultsIn bladder cancer (BC), UMB may play a role in epithelial-mesenchymal transition (and thus to progression to metastasis), as well as in effectiveness of BCG response rate. BC is also associated with changes in UMB, with bacterial richness indices increased in cancer groups compared to non-neoplastic groups and being different between NMIBC vs MIBC patients. In prostate cancer (PCa), there is an abundance in proinflammatory bacteria and uropathogens. In regard to renal cell carcinoma (RCC), penile cancer and testicular cancer there are still too few studies to draw significant conclusions about its relationship with the UMB.ConclusionsGaining a deeper understanding of UMB role in urologic tumors could aid in the development of new therapies and improve classification of patients’ risk.